Neutral reactors on shunt compensated EHV lines - Atmuri, S.R.; Thallam, R.S.; Gerlach, D.W.; Lundquist, T.G.; Selin, D.A. (IEEE Transmission and Distribution Conference, 1994, 1994)
This paper examines the applications of a neutral reactor in limiting resonance overvoltages induced on deenergized conductors due to parallel energized circuits and stuck breaker conditions. These applications are demonstrated through the planned 243 mile long Mead-Phoenix 500 kV line running on the same right of way as the existing Mead-Liberty 345 kV line. Reducing the secondary arc current during single pole reclosing is also examined. In addition to its applications, a procedure for sizing, rating and protection of the neutral reactor is explained.< >